Thermal and stability analysis of silver–water nanofluid flow over unsteady stretching sheet under the influence of heat generation/absorption at the boundary - Shah Nehad Ali; Alabduljabbar Areej Abdullah; Zeeshan; Yook Se-Jin (Nanotechnology Reviews, 2025)
The aim of this study is to examine a numerical analysis of nanofluid (NF) containing silver (Ag) nanoparticles using water (H2O) as a host fluid through an unsteady stretching sheet with stability analysis. The thermal performance of the NF is also examined in the present study, which has a significant role in aerodynamics and space sciences. A mathematical framework is created for the Ag nanofluids in terms of partial differential equations (PDEs). Through resemblance variables, the system of PDEs is made dimensionalized in terms of ordinary differential equations and then computed by a boundary-value problem fourth-order algorithm. The impacts of the physical aspects on the flow features are reported via graphs and tables. The findings show that multiple branches occur due to suction and injection. For the confirmation of the stable solution, stability examination is executed and confirms that the first branch is stable. It is reported that both NFs have high thermal efficiency; however, Ag–H2O represents significant thermal efficiencies. The present study is compared with available analyses to confirm the analysis under limited assumptions.